Low-CTE polyimide aerogel base material and preparation method thereof
By regulating the CTE and dielectric properties of polyimide aerogel, the problem of large shrinkage rate and CTE mismatch in the molding process of polyimide aerogel substrate is solved, and low CTE, low dielectric and high flexibility properties matched with copper foil are achieved, and suitable for high-frequency antenna substrates.
Patent Information
- Application Number
- CN202510854154.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-08-26
AI Technical Summary
The existing polyimide aerogel substrate has a large shrinkage rate during the molding process, and the CTE does not match the copper foil, which makes it difficult to control the shape accuracy and the material easily warped, affecting the antenna signal stability.
By preparing a low-CTE polyimide aerogel substrate, a polyamide solution containing rigid chains, a fluorine-containing polyamide solution and trace aliphatic diamines are used to form an alternating structure of "rigid domain-flexible domain" and combining porous networks and fluorine groups to regulate the matching of CTE with copper foil and reduce the dielectric constant.
CTE similar to copper foil is achieved, the dielectric constant is reduced, the flexibility and dimensional stability of the material are improved, the high-temperature impact resistance and the stability of use in humid environments are enhanced, and the application needs of high-frequency antenna substrates are met.
Smart Images

Figure CN120535950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyimide aerogel substrate and a preparation method thereof. Background Art
[0002] With the rapid development of 5G communications, equipment represented by aircraft not only requires faster signal transmission speeds and lower signal loss, but also requires the antenna substrate to be lightweight and high-strength. Among them, weight reduction is one of the key factors to improve aircraft performance, and traditional antenna substrate materials are difficult to meet these performance requirements. Early FR-4 (epoxy resin + glass fiber) is only suitable for low-frequency antennas below 6GHz due to large high-frequency losses; polytetrafluoroethylene (PTFE) has highly electronegative fluorine atoms, which results in a shorter bond length of the CF bond, thereby strengthening the van der Waals force interaction between the molecular chains. Therefore, polytetrafluoroethylene has a low dielectric constant (the dielectric constant of pure PTFE at 1MHz is 2.1). However, polytetrafluoroethylene is expensive, has a large thermal expansion coefficient, and is difficult to process. Ceramic substrates such as alumina have high dielectric constants (ε r The limitations of these materials highlight the need to develop new antenna substrate materials.
[0003] Aerogels are ideal candidate materials for antenna substrates due to their ultra-light properties and excellent dielectric properties. Although aerogels are available in a variety of types, they generally face bottlenecks such as brittleness, environmental sensitivity, and high cost. For example, silica aerogels are brittle and have low density, resulting in poor load-bearing capacity, and polyurethane aerogels have poor high-temperature resistance, making them unsuitable for use as antenna substrates. Polyimide (PI), due to its unique imide ring structure, has become one of the best-performing specialty polymers in the world. It has outstanding advantages such as high-temperature resistance (>300°C), radiation resistance, and good chemical stability. When combined with the porous structure of aerogels, the resulting PI aerogels have properties such as lightness, high strength, and high-temperature resistance. The resulting PI aerogels can be used to prepare patch antennas with lower RF loss, better impedance matching, wider bandwidth, and higher gain.
[0004] However, there are still two key problems in the practical application of PI aerogel: on the one hand, the dimensional stability is poor and the shrinkage rate during the molding process is large, which makes it difficult to control the shape accuracy of the substrate; on the other hand, the thermal expansion coefficient (CTE) does not match. The CTE of PI aerogel is significantly different from that of substrates such as copper foil, and the rigid chain aerogel substrate is almost non-deformable. It is easy to generate stress when the temperature changes, resulting in warping and even failure of the material or device, seriously affecting the stability of the antenna signal.
[0005] In summary, the core contradiction of current polyimide aerogels suitable for antenna substrates lies in: the flexible chains of existing polyimide aerogels have large shrinkage and a CTE mismatch with copper foil, while the rigid chain aerogel substrates are almost indeformable. Therefore, there is an urgent need to develop a polyimide aerogel substrate suitable for antenna substrates with a CTE that matches copper antennas, while also exhibiting low shrinkage, low dielectric constant, and a certain degree of flexibility. Summary of the Invention
[0006] The present invention aims to solve the problems of the thermal expansion coefficient of existing thermoplastic polyimide aerogel not matching that of copper foil, the rigid chain aerogel substrate being unable to be deformed, and the large shrinkage rate during the molding process of the flexible chain aerogel substrate, and further provide a low CTE polyimide aerogel substrate and a preparation method thereof.
[0007] A low CTE polyimide aerogel substrate is prepared by 100 parts by mass of a polyamic acid salt solution containing a rigid chain, 50 to 100 parts by mass of a polyamic acid salt solution containing fluorine, and 0.5 to 2 parts by mass of an aliphatic diamine.
[0008] The polyamic acid salt solution containing rigid chains is prepared from tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:(0.9-1.2); the molar ratio of the aromatic diamine to the tertiary amine A is 1:(0.05-2); the mass ratio of the total mass of the aromatic diamine and aromatic dianhydride A to the solvent A is 1:(2-10);
[0009] The repeating unit structural formula of the polyamic acid in the polyamic acid salt solution containing a rigid chain is: x=10-90, R is a tertiary amine A;
[0010] The fluorine-containing polyamic acid salt solution is prepared from a tertiary amine B, a fluorine-containing diamine, an aromatic dianhydride B, and a solvent B; the molar ratio of the fluorine-containing diamine to the aromatic dianhydride B is 1:(0.9-1.2); the molar ratio of the fluorine-containing diamine to the tertiary amine B is 1:(0.05-2); the mass ratio of the total mass of the fluorine-containing diamine and the aromatic dianhydride B to the solvent B is 1:(2-10);
[0011] The repeating unit structural formula of the polyamic acid in the fluorine-containing polyamic acid salt solution is:
[0012] y=10~90, R is a tertiary amine B.
[0013] A method for preparing a low CTE polyimide aerogel substrate is carried out according to the following steps:
[0014] 1. Preparation of polyamic acid salt solution containing rigid chains:
[0015] ① Weigh tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; mix solvent A and tertiary amine A to obtain a solvent A / tertiary amine A mixture;
[0016] The molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:(0.9-1.2); the molar ratio of the aromatic diamine to the tertiary amine A is 1:(0.05-2); the mass ratio of the total mass of the aromatic diamine and the aromatic dianhydride A to the solvent A is 1:(2-10);
[0017] ② Under nitrogen atmosphere, room temperature and stirring conditions, the solvent A / tertiary amine A mixture and the aromatic diamine are mixed for 0.5h to 1h to obtain a mixture A, the reaction temperature is raised to 40°C to 80°C, and under nitrogen atmosphere, the temperature is 40°C to 80°C and stirring conditions, the aromatic dianhydride A is added to the mixture A in three portions and stirred for 2h to 5h. Finally, under nitrogen atmosphere, the reaction temperature is lowered from 40°C to 80°C to 25°C to 30°C, and the mixture is allowed to stand for 5h to 10h to obtain a polyamic acid salt solution containing a rigid chain;
[0018] 2. Preparation of fluorine-containing polyamic acid salt solution:
[0019] ① Weigh tertiary amine B, fluorinated diamine, aromatic dianhydride B and solvent B; mix solvent B and tertiary amine B to obtain a solvent B / tertiary amine B mixture;
[0020] The molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:(0.9-1.2); the molar ratio of the fluorinated diamine to the tertiary amine B is 1:(0.05-2); the mass ratio of the total mass of the fluorinated diamine and the aromatic dianhydride B to the solvent B is 1:(2-10);
[0021] ② Under nitrogen atmosphere, room temperature and stirring conditions, the solvent B / tertiary amine B mixture and the fluorinated diamine are mixed for 0.5h to 1h to obtain a mixture B, the reaction temperature is raised to 40°C to 80°C, and under nitrogen atmosphere, the temperature is 40°C to 80°C and stirring conditions, the aromatic dianhydride B is added to the mixture B in three portions and stirred for 2h to 5h. Finally, under nitrogen atmosphere, the reaction temperature is lowered from 40°C to 65°C to 25°C to 30°C, and the mixture is allowed to stand for 5h to 10h to obtain a fluorinated polyamic acid salt solution;
[0022] 3. Weighing:
[0023] Weigh 100 parts of a polyamic acid salt solution containing a rigid chain, 50 to 100 parts of a polyamic acid salt solution containing fluorine, and 0.5 to 2 parts of an aliphatic diamine according to the mass ratio;
[0024] 4. Blending:
[0025] Under the conditions of a temperature of 40° C. to 80° C., mechanical stirring and ultrasonic dispersion, the weighed aliphatic diamine is added to the polyamic acid salt solution containing a rigid chain, and stirred for 2 h to 5 h. Then, under the conditions of a temperature of 40° C. to 80° C., mechanical stirring and ultrasonic dispersion, the fluorine-containing polyamic acid salt solution is added. Finally, the reaction temperature is lowered from 40° C. to 80° C. to 25° C. to 30° C. to obtain a reaction system.
[0026] 5. Freeze drying:
[0027] The reaction system is placed in a mold, and then a freeze dryer is used to freeze the reaction system at a freezing temperature of -50°C to -10°C for 10 hours to 15 hours, and finally freeze-dried at a temperature of -30°C to -10°C for 60 hours to 100 hours to obtain a polyimide precursor aerogel.
[0028] 6. Thermal imidization reaction:
[0029] The polyimide precursor aerogel is subjected to a thermal imidization reaction to obtain a low CTE polyimide aerogel substrate.
[0030] The beneficial effects of the present invention are:
[0031] The present invention regulates the CTE of PI aerogel at the molecular level. The chain segments constructed with rigid monomers such as p-phenylenediamine and 3,3′,4,4′-biphenyltetracarboxylic dianhydride (S-BPDA) have high planarity and conjugated structure. The molecular chains form a tight physical cross-linking network through π-π stacking, which significantly suppresses the thermal motion amplitude of the chain segments when the temperature rises. Surprisingly, even in the ternary block copolymer system, the two -CF3 in TFMB still form nanocavities of 0.5 to 1.0 nm between the molecular chains due to steric hindrance. The van der Waals radius of -CF3 is It will push away the adjacent molecular chains, forming a local low-density area, absorbing thermal vibration energy, thereby inhibiting thermal expansion. In addition, the porous network of the aerogel can absorb thermal stress, and the local expansion of the pore wall is buffered by the pores, which will inhibit expansion and reduce the overall CTE. And the fatty chains with trace amounts of fatty diamines will form flexible micro-regions, which will undergo micro-phase separation with the rigid segments (S-BPDA / TFMB or S-BPDA / PDA) to form an alternating structure of "rigid domain-flexible domain". Through the geometric constraints of the rigid chain, the free volume buffering of the fluorine group, and the stress dispersion of the flexible chain, the "controllable regulation" of CTE can be achieved, thereby obtaining a CTE close to that of copper foil.
[0032] The present invention reduces the dielectric constant by designing the molecular structure and introducing a microporous structure. The fluorine group and the porous structure double the dielectric constant. The segment 2 (TFMB) in the present invention contains two trifluoromethyl groups in the para position. The highly electronegative -CF3 has a low dipole polarization (β polarization) ability, which reduces the conjugation of the electron cloud and the formation of electron transfer complexes, so that the PI molecular chain exhibits a lower polarization. In addition, the large volume of the -CF3 group will reduce the polarization density, thereby further reducing the dielectric constant. Porous PI combines the high thermal stability and mechanical properties of PI itself with the excellent characteristics of high specific surface area and low dielectric properties of porous materials. PI aerogel with high porosity and high specific surface area, due to the dielectric constant of air (ε r ≈1) is much lower than that of most solid materials (such as polymers r Usually between 2-4). Thus, the overall polarization ability of the material is effectively reduced, thereby reducing the dielectric constant. The TFMB monomer and PI aerogel in the present invention synergistically reduce the dielectric constant, and the fluorine group reduces the ε of the PI body. r , and the porous structure further reduces the overall dielectric properties, achieving an ultra-low dielectric constant. It is worth noting that the hydrophobic properties imparted by the fluorinated groups can also enhance its stability as a dielectric material in humid environments. Since water has a high dielectric constant (ε r ≈80). Traditional polyimide easily absorbs water, which leads to deterioration of dielectric properties. The adsorbed water molecules will cause the dielectric constant of the material to increase abnormally due to high polarization. The introduction of fluorinated groups suppresses this phenomenon through the dual mechanisms of electron shielding effect and surface energy regulation. First, the high electronegativity of the CF bond (χ = 4.0) and low polarizability The electron cloud density on the surface of the material is reduced, so that the hydrogen bond adsorption energy of water molecules is reduced, and the adsorption of water molecules through hydrogen bonds is inhibited. Secondly, the fluorine-containing groups are arranged in a direction on the surface of the material to form a low-energy barrier (surface energy γ<20mN / m), which significantly reduces the surface energy of the material and increases the contact angle through the Cassie-Baxter state, thereby reducing the water absorption rate.
[0033] The present invention imparts local motion ability to the molecular chain by the addition of flexible chains, improves the flexibility of the molecular chain, adjusts the CTE of PI aerogel to be closer to copper foil (17ppm / k), reduces interfacial thermal mismatch stress, and improves metal patch adhesion after high and low temperature cycling. And the flexible segment undergoes local segment motion at high temperatures, which can relax the thermal stress accumulated between the rigid chains and improve high temperature impact tolerance. The present invention coordinates the stacking behavior and free volume distribution of the molecular chain by block copolymerization of a polyimide precursor containing a rigid chain, a fluorine-containing polyimide precursor, and an aliphatic diamine, achieving a breakthrough in the triple performance of low CTE, low dielectric, and high flexibility of PI aerogel, filling the technical gap of high-frequency flexible antenna substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a physical picture of the low CTE polyimide aerogel substrate prepared in Example 1;
[0035] Figure 2 This is a scanning electron microscope image of the low CTE polyimide aerogel substrate prepared in Example 2;
[0036] Figure 3 This is an infrared spectrum of the low CTE polyimide aerogel substrate prepared in Example 1;
[0037] Figure 4 This is the TMA image of the low CTE polyimide aerogel substrate prepared in Example 3. DETAILED DESCRIPTION
[0038] Specific embodiment 1: A low CTE polyimide aerogel substrate of this embodiment is prepared by 100 parts by mass of a polyamic acid salt solution containing a rigid chain, 50 to 100 parts by mass of a polyamic acid salt solution containing a fluorine, and 0.5 to 2 parts by mass of an aliphatic diamine;
[0039] The polyamic acid salt solution containing rigid chains is prepared from tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:(0.9-1.2); the molar ratio of the aromatic diamine to the tertiary amine A is 1:(0.05-2); the mass ratio of the total mass of the aromatic diamine and aromatic dianhydride A to the solvent A is 1:(2-10);
[0040] The repeating unit structural formula of the polyamic acid in the polyamic acid salt solution containing a rigid chain is: x=10-90, R is a tertiary amine A;
[0041] The fluorine-containing polyamic acid salt solution is prepared from a tertiary amine B, a fluorine-containing diamine, an aromatic dianhydride B, and a solvent B; the molar ratio of the fluorine-containing diamine to the aromatic dianhydride B is 1:(0.9-1.2); the molar ratio of the fluorine-containing diamine to the tertiary amine B is 1:(0.05-2); the mass ratio of the total mass of the fluorine-containing diamine and the aromatic dianhydride B to the solvent B is 1:(2-10);
[0042] The repeating unit structural formula of the polyamic acid in the fluorine-containing polyamic acid salt solution is:
[0043] y=10~90, R is a tertiary amine B.
[0044] The structural formula of the low CTE polyimide aerogel substrate is:
[0045]
[0046] The 1 is a polyimide unit formed by a polyamic acid salt solution containing a rigid chain;
[0047] The 2 is a polyimide unit formed by a fluorine-containing polyamic acid salt solution;
[0048] The Contains aliphatic diamine.
[0049] This specific embodiment proposes a modified PI aerogel substrate. By optimizing the material structure and composite process, it significantly improves dimensional stability and reduces CTE while maintaining its lightweight and high-strength properties, thereby achieving good matching with copper circuits and meeting the application requirements of high-performance antenna substrates.
[0050] The beneficial effects of this specific embodiment are:
[0051] This specific embodiment regulates the CTE of PI aerogel at the molecular level. The chain segments constructed with rigid monomers such as p-phenylenediamine and 3,3′,4,4′-biphenyltetracarboxylic dianhydride (S-BPDA) have high planarity and conjugated structure. The molecular chains form a tight physical cross-linking network through π-π stacking, which significantly suppresses the thermal motion amplitude of the chain segments when the temperature rises. Surprisingly, even in the ternary block copolymer system, the two -CF3 in TFMB still form nanocavities of 0.5 to 1.0 nm between the molecular chains through steric hindrance. The van der Waals radius of -CF3 is It will push away the adjacent molecular chains, forming a local low-density area, absorbing thermal vibration energy, thereby inhibiting thermal expansion. In addition, the porous network of the aerogel can absorb thermal stress, and the local expansion of the pore wall is buffered by the pores, which will inhibit expansion and reduce the overall CTE. And the fatty chains with trace amounts of fatty diamines will form flexible micro-regions, which will undergo micro-phase separation with the rigid segments (S-BPDA / TFMB or S-BPDA / PDA) to form an alternating structure of "rigid domain-flexible domain". Through the geometric constraints of the rigid chain, the free volume buffering of the fluorine group, and the stress dispersion of the flexible chain, the "controllable regulation" of CTE can be achieved, thereby obtaining a CTE close to that of copper foil.
[0052] This specific embodiment reduces the dielectric constant by molecular structure design and introducing a microporous structure. The fluorine group and the porous structure double the dielectric constant. The segment 2 (TFMB) in this specific embodiment contains two trifluoromethyl groups in the para position. The highly electronegative -CF3 has a low dipole polarization (β polarization) ability, which reduces the conjugation of the electron cloud and the formation of electron transfer complexes, so that the PI molecular chain exhibits a lower polarization. In addition, the large volume of the -CF3 group will reduce the polarization density, thereby further reducing the dielectric constant. Porous PI combines the high thermal stability and mechanical properties of PI itself with the excellent characteristics of high specific surface area and low dielectric properties of porous materials. PI aerogel with high porosity and high specific surface area, due to the dielectric constant of air (ε r ≈1) is much lower than that of most solid materials (such as polymers r Usually between 2-4). This effectively reduces the overall polarization ability of the material, thereby reducing the dielectric constant. In this embodiment, the TFMB monomer and the PI aerogel synergistically reduce the dielectric constant, and the fluorine group reduces the ε of the PI body. r , and the porous structure further reduces the overall dielectric properties, achieving an ultra-low dielectric constant. It is worth noting that the hydrophobic properties imparted by the fluorinated groups can also enhance its stability as a dielectric material in humid environments. Since water has a high dielectric constant (ε r ≈80). Traditional polyimide easily absorbs water, which leads to deterioration of dielectric properties. The adsorbed water molecules will cause the dielectric constant of the material to increase abnormally due to high polarization. The introduction of fluorinated groups suppresses this phenomenon through the dual mechanisms of electron shielding effect and surface energy regulation. First, the high electronegativity of the CF bond (χ = 4.0) and low polarizability The electron cloud density on the surface of the material is reduced, so that the hydrogen bond adsorption energy of water molecules is reduced, and the adsorption of water molecules through hydrogen bonds is inhibited. Secondly, the fluorine-containing groups are arranged in a direction on the surface of the material to form a low-energy barrier (surface energy γ<20mN / m), which significantly reduces the surface energy of the material and increases the contact angle through the Cassie-Baxter state, thereby reducing the water absorption rate.
[0053] This specific embodiment, by adding flexible chains, gives the molecular chains the ability to move locally, improves the flexibility of the molecular chains, adjusts the CTE of the PI aerogel to be closer to copper foil (17ppm / k), reduces the interfacial thermal mismatch stress, and improves the adhesion of the metal patch after high and low temperature cycles. In addition, the flexible segments undergo local segment movement at high temperatures, which can relax the thermal stress accumulated between the rigid chains and improve the high-temperature impact tolerance. This specific embodiment synergistically regulates the stacking behavior and free volume distribution of the molecular chains through block copolymerization of a polyimide precursor containing a rigid chain, a fluorine-containing polyimide precursor, and an aliphatic diamine, thereby achieving a breakthrough in the triple performance of PI aerogel in low CTE, low dielectric, and high flexibility, filling the technical gap in high-frequency flexible antenna substrates.
[0054] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the solvent A and solvent B are both water. Other aspects are the same as specific embodiment 1.
[0055] Specific embodiment 3: This embodiment differs from specific embodiments 1 or 2 in that the tertiary amine A and tertiary amine B are each one of triethylamine, trialkyl tertiary amine, octadecyldimethyl tertiary amine, and dodecyldimethyl tertiary amine, or a mixture thereof. Other aspects are the same as specific embodiments 1 or 2.
[0056] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the aromatic diamine is p-phenylenediamine and the fluorine-containing diamine is 4,4′-diamino-2,2′-bis(trifluoromethyl)biphenyl. Other aspects are the same as specific embodiments 1 to 3.
[0057] The structural formula of the p-phenylenediamine is The structural formula of the 4,4′-diamino-2,2′-bis(trifluoromethyl)biphenyl is
[0058] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the aromatic dianhydride A and aromatic dianhydride B are both 3,3′,4,4′-biphenyltetracarboxylic dianhydride. Other aspects are the same as specific embodiments 1 to 4.
[0059] The structural formula of the 3,3′,4,4′-biphenyltetracarboxylic dianhydride is
[0060] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the aliphatic diamine is 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine or 1,12-dodecanediamine. Other aspects are the same as specific embodiments 1 to 5.
[0061] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the aliphatic diamine is 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, or 1,12-dodecanediamine. Other aspects are the same as specific embodiments 1 to 6.
[0062] Specific embodiment eight: This embodiment provides a method for preparing a low CTE polyimide aerogel substrate, which is carried out according to the following steps:
[0063] 1. Preparation of polyamic acid salt solution containing rigid chains:
[0064] ① Weigh tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; mix solvent A and tertiary amine A to obtain a solvent A / tertiary amine A mixture;
[0065] The molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:(0.9-1.2); the molar ratio of the aromatic diamine to the tertiary amine A is 1:(0.05-2); the mass ratio of the total mass of the aromatic diamine and the aromatic dianhydride A to the solvent A is 1:(2-10);
[0066] ② Under nitrogen atmosphere, room temperature and stirring conditions, the solvent A / tertiary amine A mixture and the aromatic diamine are mixed for 0.5h to 1h to obtain a mixture A, the reaction temperature is raised to 40°C to 80°C, and under nitrogen atmosphere, the temperature is 40°C to 80°C and stirring conditions, the aromatic dianhydride A is added to the mixture A in three portions and stirred for 2h to 5h. Finally, under nitrogen atmosphere, the reaction temperature is lowered from 40°C to 80°C to 25°C to 30°C, and the mixture is allowed to stand for 5h to 10h to obtain a polyamic acid salt solution containing a rigid chain;
[0067] 2. Preparation of fluorine-containing polyamic acid salt solution:
[0068] ① Weigh tertiary amine B, fluorinated diamine, aromatic dianhydride B and solvent B; mix solvent B and tertiary amine B to obtain a solvent B / tertiary amine B mixture;
[0069] The molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:(0.9-1.2); the molar ratio of the fluorinated diamine to the tertiary amine B is 1:(0.05-2); the mass ratio of the total mass of the fluorinated diamine and the aromatic dianhydride B to the solvent B is 1:(2-10);
[0070] ② Under nitrogen atmosphere, room temperature and stirring conditions, the solvent B / tertiary amine B mixture and the fluorinated diamine are mixed for 0.5h to 1h to obtain a mixture B, the reaction temperature is raised to 40°C to 80°C, and under nitrogen atmosphere, the temperature is 40°C to 80°C and stirring conditions, the aromatic dianhydride B is added to the mixture B in three portions and stirred for 2h to 5h. Finally, under nitrogen atmosphere, the reaction temperature is lowered from 40°C to 65°C to 25°C to 30°C, and the mixture is allowed to stand for 5h to 10h to obtain a fluorinated polyamic acid salt solution;
[0071] 3. Weighing:
[0072] Weigh 100 parts of a polyamic acid salt solution containing a rigid chain, 50 to 100 parts of a polyamic acid salt solution containing fluorine, and 0.5 to 2 parts of an aliphatic diamine according to the mass ratio;
[0073] 4. Blending:
[0074] Under the conditions of a temperature of 40° C. to 80° C., mechanical stirring and ultrasonic dispersion, the weighed aliphatic diamine is added to the polyamic acid salt solution containing a rigid chain, and stirred for 2 h to 5 h. Then, under the conditions of a temperature of 40° C. to 80° C., mechanical stirring and ultrasonic dispersion, the fluorine-containing polyamic acid salt solution is added. Finally, the reaction temperature is lowered from 40° C. to 80° C. to 25° C. to 30° C. to obtain a reaction system.
[0075] 5. Freeze drying:
[0076] The reaction system is placed in a mold, and then a freeze dryer is used to freeze the reaction system at a freezing temperature of -50°C to -10°C for 10 hours to 15 hours, and finally freeze-dried at a temperature of -30°C to -10°C for 60 hours to 100 hours to obtain a polyimide precursor aerogel.
[0077] 6. Thermal imidization reaction:
[0078] The polyimide precursor aerogel is subjected to a thermal imidization reaction to obtain a low CTE polyimide aerogel substrate.
[0079] Specific embodiment 9: This embodiment differs from specific embodiment 8 in that: in step 1②, aromatic dianhydride A is added to mixture A in three portions at 1 / 2, 1 / 4, and 1 / 4 of the mass; and in step 2②, aromatic dianhydride B is added to mixture B in three portions at 1 / 2, 1 / 4, and 1 / 4 of the mass. Other steps are the same as specific embodiment 8.
[0080] Specific embodiment 10: This embodiment differs from specific embodiment 8 or 9 in that the thermal imidization reaction described in step 6 is specifically carried out according to the following steps: first, maintaining the temperature at 70°C to 100°C for 2 to 4 hours, then maintaining the temperature at 180°C to 230°C for 2 to 4 hours, then maintaining the temperature at 300°C to 320°C for 2 to 6 hours, and finally maintaining the temperature at 400°C to 420°C for 2 to 3 hours. Other steps are the same as specific embodiment 8 or 9.
[0081] The following examples are used to verify the beneficial effects of the present invention:
[0082] Example 1:
[0083] A low CTE polyimide aerogel substrate is prepared by 100 parts by mass of a polyamic acid salt solution containing a rigid chain, 50 parts by mass of a polyamic acid salt solution containing fluorine, and 2 parts by mass of aliphatic diamine;
[0084] The polyamic acid salt solution containing rigid chains is prepared from tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.05; the molar ratio of the aromatic diamine to the tertiary amine A is 1:2; the mass ratio of the total mass of the aromatic diamine and aromatic dianhydride A to the solvent A is 1:10;
[0085] The repeating unit structural formula of the polyamic acid in the polyamic acid salt solution containing a rigid chain is: x=20, R is a tertiary amine A;
[0086] The fluorine-containing polyamic acid salt solution is prepared from a tertiary amine B, a fluorine-containing diamine, an aromatic dianhydride B, and a solvent B; the molar ratio of the fluorine-containing diamine to the aromatic dianhydride B is 1:1.05; the molar ratio of the fluorine-containing diamine to the tertiary amine B is 1:2; and the mass ratio of the total mass of the fluorine-containing diamine and the aromatic dianhydride B to the solvent B is 1:10;
[0087] The repeating unit structural formula of the polyamic acid in the fluorine-containing polyamic acid salt solution is:
[0088] y=20, R is a tertiary amine B.
[0089] The solvent A and solvent B are both water.
[0090] The tertiary amine A and the tertiary amine B are both triethylamine.
[0091] The aromatic diamine is p-phenylenediamine (p-PDA); the fluorine-containing diamine is 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB).
[0092] The aromatic dianhydride A and aromatic dianhydride B are 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA).
[0093] The aliphatic diamine is 1,6-hexanediamine.
[0094] A method for preparing a low CTE polyimide aerogel substrate is carried out according to the following steps:
[0095] 1. Preparation of polyamic acid salt solution containing rigid chains:
[0096] ① Weigh tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; mix solvent A and tertiary amine A to obtain a solvent A / tertiary amine A mixture;
[0097] ② Under nitrogen atmosphere, room temperature and stirring speed of 300 rpm, the solvent A / tertiary amine A mixture and aromatic diamine were mixed for 1 hour to obtain mixture A, and the reaction temperature was raised to 60°C. Under nitrogen atmosphere, temperature of 60°C and stirring speed of 300 rpm, aromatic dianhydride A was added to mixture A in three portions and stirred for 4 hours. Finally, under nitrogen atmosphere, the reaction temperature was lowered from 60°C to 25°C and allowed to stand for 6 hours to obtain a polyamic acid salt solution containing rigid chains;
[0098] 2. Preparation of fluorine-containing polyamic acid salt solution:
[0099] ① Weigh tertiary amine B, fluorinated diamine, aromatic dianhydride B and solvent B; mix solvent B and tertiary amine B to obtain a solvent B / tertiary amine B mixture;
[0100] ② Under nitrogen atmosphere, room temperature and stirring speed of 300 rpm, the solvent B / tertiary amine B mixture and the fluorinated diamine were mixed for 1 hour to obtain a mixture B, the reaction temperature was raised to 60 ° C, and under nitrogen atmosphere, temperature of 60 ° C and stirring speed of 300 rpm, aromatic dianhydride B was added to the mixture B in three portions and stirred for 4 hours. Finally, under nitrogen atmosphere, the reaction temperature was lowered from 60 ° C to 25 ° C, and the mixture was allowed to stand for 6 hours to obtain a fluorinated polyamic acid salt solution;
[0101] 3. Weighing:
[0102] Weigh 100 parts of a polyamic acid salt solution containing a rigid chain, 50 parts of a polyamic acid salt solution containing fluorine, and 2 parts of aliphatic diamine according to their mass ratios;
[0103] 4. Blending:
[0104] Under the conditions of a temperature of 60°C, a mechanical stirring speed of 400 rpm and an ultrasonic dispersion power of 50 W, the weighed aliphatic diamine was added to the polyamic acid salt solution containing a rigid chain and stirred for 4 hours. Then, under the conditions of a temperature of 60°C, a mechanical stirring speed of 400 rpm and an ultrasonic dispersion power of 50 W, the fluorine-containing polyamic acid salt solution was added. Finally, the reaction temperature was lowered from 60°C to 25°C to obtain a reaction system.
[0105] 5. Freeze drying:
[0106] The reaction system was placed in a silica gel mold, and then frozen in a freeze dryer at a freezing temperature of -20°C for 15 hours, and finally freeze-dried at a temperature of -20°C for 90 hours to obtain a polyimide precursor aerogel;
[0107] 6. Thermal imidization reaction:
[0108] The polyimide precursor aerogel is subjected to a thermal imidization reaction to obtain a low CTE polyimide aerogel substrate.
[0109] Step 1② Add aromatic dianhydride A to mixture A in three portions at 1 / 2, 1 / 4, and 1 / 4 of the mass; Step 2② Add aromatic dianhydride B to mixture B in three portions at 1 / 2, 1 / 4, and 1 / 4 of the mass.
[0110] The thermal imidization reaction described in step six is specifically carried out according to the following steps: first, the temperature is kept constant at 100°C for 4 hours, then the temperature is kept constant at 200°C for 3 hours, then the temperature is kept constant at 300°C for 5 hours, and finally the temperature is kept constant at 400°C for 2 hours.
[0111] Example 2: This example differs from Example 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.02, and the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:1.02. Other aspects are the same as Example 1.
[0112] Example 3: This example differs from Example 1 in that the aliphatic diamine is 1,8-octanediamine; the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.02; and the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:1.02. Other aspects are the same as Example 1.
[0113] Example 4: This example differs from Example 1 in that the aliphatic diamine is 1,10-decanediamine; the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.02; and the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:1.02. Other aspects are the same as Example 1.
[0114] Example 5: This example differs from Example 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.01, and the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:1.03. Other aspects are the same as Example 1.
[0115] Example 6: This example differs from Example 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.03, and the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:1.01. Other aspects are the same as Example 1.
[0116] Example 7: This example differs from Example 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.01, and the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:1.01. Other aspects are the same as Example 1.
[0117] Comparative Example 1: This comparative example differs from Example 1 in that: tertiary amine A is omitted in step 1 (1); the molar ratio of aromatic diamine to aromatic dianhydride A in step 1 (1) is 1:1; and the fluorine-containing polyamic acid salt solution and aliphatic diamine are omitted in step 3. All other steps are the same as in Example 1.
[0118] Comparative Example 2: This comparative example differs from Example 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.02; the molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:0.98; and the aliphatic diamine is omitted in step 3. Other steps are the same as in Example 1.
[0119] Comparative Example 3: This comparative example differs from Example 1 in that the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:1.02 and the fluorine-containing polyamic acid salt solution is omitted in step 3. Other steps are the same as Example 1.
[0120] Table 1 Raw material system and process parameters of low CTE polyimide aerogel substrate
[0121]
[0122]
[0123] The polyimide aerogel substrates prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to performance tests:
[0124] 1. Density: Use the weight method to weigh 0.5×2×2cm 3 The weight and volume of the square block were calculated, the density was calculated, and the average value was taken after the sample was tested three times;
[0125] 2. Elongation at break test: The elongation at break of the polyimide aerogel substrate was tested using an electronic universal material testing machine. The sample preparation standard was based on ASTM D638.
[0126] 3. Dynamic bending test: IEC62715-6-1 method is used for testing. The required sample size is: length × width × thickness is 100mm × 20mm × 0.1mm. The bending radius of the test is 2mm (simulating extreme conditions). The test frequency is 1Hz and the number of tests is 500.
[0127] 4. Contact angle test: Using ASTM D7334 standard, the contact angle of the polyimide aerogel substrate was measured using a contact angle meter;
[0128] 5. Water absorption test: Dry the polyimide aerogel substrate in a vacuum oven at 80°C to constant weight (mass is recorded as W0). Then immerse the sample in 25°C deionized water for 24 hours. Remove and absorb the surface moisture with filter paper. Immediately weigh (mass is recorded as W1). Calculate water absorption: Water absorption (%) = [(W1-W0) / W0] × 100%;
[0129] 6. Coefficient of thermal expansion (CTE) test:
[0130] (1) Dry CTE test: Cut the polyimide aerogel substrate into rectangular specimens of standard size (length 25 mm, width 4 mm, thickness 0.5 mm), and place the specimen in a vacuum oven at 80°C for at least 24 hours until constant weight is reached to remove adsorbed moisture and residual solvent. The tensile mode test was performed using a TMA (thermomechanical analyzer); the heating rate was 10°C / min, the test temperature range was 25°C to 380°C, and when calculating the CTE, the linear expansion region from 25°C to the starting point of the glass transition temperature (Tg) was taken (usually 25°C to 220°C, which needs to be determined based on the actual curve). The thermal expansion coefficient of the polyimide aerogel substrate is recorded as α1.
[0131] (2) Wet state coefficient of thermal expansion (CTE) test, wherein the sample pretreatment steps are as follows: the polyimide aerogel substrate is cut into rectangular specimens of standard size (length 25 mm, width 4 mm, thickness 0.5 mm), and placed in a constant temperature and humidity chamber, and the target relative humidity (RH) is set: the CTE at 85% RH, 90% RH, and 95% RH are tested respectively, and the mass change is monitored by weighing method until the moisture absorption equilibrium is reached. The sample after moisture absorption is quickly transferred to a sealed container to avoid moisture loss before the test. During the wet state CTE test, a thermomechanical analyzer equipped with a humidity control module is used, with a heating rate of 10℃ / min and a range of -50℃ to 150℃ (this temperature range covers common ambient temperature fluctuations and avoids excessive water loss at high temperature that affects the results), and the target relative humidity is monitored and maintained in real time.
[0132] 7. After high temperature shock and high and low temperature cycling, the metal patch peel strength test is performed. The preparation method of the metal patch is as follows: first, the polyimide aerogel substrate is treated with plasma (power 100W, time 2min) to remove organic matter and activate the surface, and then a layer of metal Cu is deposited on the surface of the aerogel substrate by a magnetron sputtering process. A dense transition layer is constructed on the aerogel surface to enhance the interface bonding strength, and copper foil is covered on the Cu layer. The substrate sample after metal patch is obtained by hot pressing at 200°C and 5MPa for 1h. The substrate sample after metal patch is first kept in a low temperature environment of -55°C for 30min, and then rapidly heated to 300°C at a rate of 5°C / min to simulate sudden thermal shock (ΔT = 355°C), and maintained at high temperature for 30min. The above high and low temperature cycle is repeated 100 times to examine the interface stability of the material under long-term thermal shock conditions. The substrate sample after metal patch is subjected to a 90° peel test to evaluate the bonding strength between the metal patch and the substrate. Finally, the interface delamination is observed using an optical microscope.
[0133] 8. Reflection angle test: Use a laser reflectometer to measure the deviation angle of the reflected light spot when the incident angle is 45°;
[0134] 9. Relative dielectric properties test: The relative dielectric properties were tested using an Agilent Technologies Inc-E5071C vector network analyzer using the waveguide method at the X-band (8.2-12.4 GHz) frequency.
[0135] 10. Relative dielectric constant under condensation water cycle test: The polyimide aerogel substrate was placed in a condensation-drying cycle environment. The experimental conditions were: 40°C / 95% RH for 4 hours, 25°C / 50% RH for 2 hours, and the above two-stage switching was repeated 50 times to test the stability of the dielectric properties of the material. The frequency was X-band (8.2GHz-12.4GHz).
[0136] 11. Volume shrinkage: The shrinkage is calculated by taking the length, width and height of the reaction system prepared in step 4 when poured into the silicone mold as the initial length and calculating the initial volume. The length, width and height of the sample when imidized to 400°C are taken as the final length and calculating the final volume shrinkage. The calculation formula of the sample shrinkage is: Shrinkage (%) = [(initial volume - final volume) / initial volume] × 100%.
[0137] Table 2 Key performance index test of low CTE polyimide aerogel substrate
[0138]
[0139]
[0140]
[0141] From the test results of Examples 1 to 7 and Comparative Examples 1 to 3, it can be seen that the ternary collaborative design (rigid chain + fluorine group + flexible chain) is the key to achieving low CTE, low dielectric constant and high flexibility at the same time: Examples 1 to 7 suppress thermal expansion (CTE 16.7-17.5ppm / k) by π-π stacking of rigid chains (S-BPDA / PDA), and the nanocavities of fluorine groups (TFMB) reduce the dielectric constant (ε r <1.2), and aliphatic diamines (such as 1,6-hexanediamine) form flexible micro-regions (no cracks after 500 bends, and the elongation at break is ≥1.3%). The contact angles of Examples 1 to 7 are all greater than 120°, and the water absorption rate is less than 1.0%, which is attributed to the fact that the fluorine group can significantly inhibit the adsorption of water molecules. The CTE increase of Examples 1 to 7 at 85%-95% RH is small (17.0→18.4ppm / ℃), which is because the fluorine group and the flexible chain buffer the hygroscopic expansion stress. The dielectric constant of Examples 1 to 7 under the condensation water cycle test changes very little (Δε r <0.05), which is because the presence of fluorine groups enhances the stability of the dielectric material in a humid environment. The above shows that the comprehensive performance of the embodiment is excellent; while the comparative example 1 (pure rigid chain) lacks fluorine groups and flexible chains, resulting in a too high CTE (28ppm·k -1 ), dielectric difference (ε r =1.89), the lowest elongation at break (0.8%), high brittleness, the lowest contact angle (75°), the highest water absorption rate (3.5%), and a CTE of up to 34ppm / °C at 95%RH, indicating that thermal expansion is out of control after moisture absorption. Comparative Example 2 lacks flexible chains, and although the elongation at break is high (2.2%), the dynamic bending performance is poor (partial cracks), indicating that the material is not tough enough. Comparative Example 3 lacks the free volume control and hydrophobic effect of the fluorine group, and the CTE (19ppm·k -1 )) and dielectric constant (ε r =1.8) is suboptimal, with increased water absorption (2.5%) leading to decreased wet stability and a volume shrinkage of up to 32%. This fully demonstrates the irreplaceable synergy of the three components: the rigid chain provides skeletal support, the fluorine groups optimize dielectric and thermal expansion, and the flexible chain imparts deformation capability. The lack of any of these three components will result in performance shortcomings.
[0142] Figure 1 This is a physical picture of the low CTE polyimide aerogel substrate prepared in Example 1. As can be seen from the figure, the prepared low CTE polyimide aerogel substrate has excellent geometric flatness, and no obvious deformation or warping is observed.
[0143] Figure 2This is a scanning electron microscope image of the low CTE polyimide aerogel substrate prepared in Example 2. As can be seen from the figure, the overall structure of the prepared low CTE polyimide aerogel substrate is continuous and uniform, without macroscopic phase separation or structural instability.
[0144] Figure 3 This is the infrared spectrum of the low CTE polyimide aerogel substrate prepared in Example 1; as shown in the figure, at 1787 cm -1 (imide C=O asymmetric stretching vibration), 1702 cm -1 (imide C=O symmetric stretching vibration), 1347 cm -1 (CN stretching vibration) and 1084cm -1 and 734cm -1 The characteristic peak appearing near (imine bond CNC stretching vibration) confirmed the successful imidization of the substrate.
[0145] Figure 4 This is a TMA diagram of the low CTE polyimide aerogel substrate prepared in Example 3. As can be seen from the figure, the linear expansion coefficient of the polyimide aerogel substrate is 16.7 ppm·k from 25°C to the starting point of the glass transition temperature (Tg) (220°C). -1 , indicating that it has excellent dimensional stability in this temperature range.
Claims
1. A low CTE polyimide aerogel substrate, characterized in that It is prepared from 100 parts by mass of a polyamic acid salt solution containing a rigid chain, 50 to 100 parts by mass of a polyamic acid salt solution containing fluorine and 0.5 to 2 parts by mass of an aliphatic diamine. The polyamic acid salt solution containing rigid chains is prepared from tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; the molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:(0.9-1.2); the molar ratio of the aromatic diamine to the tertiary amine A is 1:(0.05-2); the mass ratio of the total mass of the aromatic diamine and aromatic dianhydride A to the solvent A is 1:(2-10); The repeating unit structural formula of the polyamic acid in the polyamic acid salt solution containing a rigid chain is: x=10-90, R is a tertiary amine A; The fluorine-containing polyamic acid salt solution is prepared from a tertiary amine B, a fluorine-containing diamine, an aromatic dianhydride B, and a solvent B; the molar ratio of the fluorine-containing diamine to the aromatic dianhydride B is 1:(0.9-1.2); the molar ratio of the fluorine-containing diamine to the tertiary amine B is 1:(0.05-2); the mass ratio of the total mass of the fluorine-containing diamine and the aromatic dianhydride B to the solvent B is 1:(2-10); The repeating unit structural formula of the polyamic acid in the fluorine-containing polyamic acid salt solution is: y=10~90, R is a tertiary amine B.
2. A low CTE polyimide aerogel substrate according to claim 1, characterized in that The solvent A and solvent B are both water.
3. The low CTE polyimide aerogel substrate according to claim 1, characterized in that The tertiary amine A and the tertiary amine B are each one of triethylamine, trialkyl tertiary amine, octadecyldimethyl tertiary amine and dodecyldimethyl tertiary amine or a mixture of several thereof.
4. The low CTE polyimide aerogel substrate according to claim 1, characterized in that The aromatic diamine is p-phenylenediamine; the fluorine-containing diamine is 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl.
5. The low CTE polyimide aerogel substrate according to claim 1, characterized in that The aromatic dianhydride A and aromatic dianhydride B are both 3,3',4,4'-biphenyltetracarboxylic dianhydride.
6. The low CTE polyimide aerogel substrate according to claim 1, characterized in that The aliphatic diamine is a fatty diamine with a carbon chain length of ≥6 and ≤12.
7. The low CTE polyimide aerogel substrate according to claim 6, characterized in that The aliphatic diamine is 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine or 1,12-dodecanediamine.
8. The method for preparing a low CTE polyimide aerogel substrate according to claim 1, wherein It is carried out in the following steps:
1. Preparation of polyamic acid salt solution containing rigid chains: ① Weigh tertiary amine A, aromatic diamine, aromatic dianhydride A and solvent A; mix solvent A and tertiary amine A to obtain a solvent A / tertiary amine A mixture; The molar ratio of the aromatic diamine to the aromatic dianhydride A is 1:(0.9-1.2); the molar ratio of the aromatic diamine to the tertiary amine A is 1:(0.05-2); the mass ratio of the total mass of the aromatic diamine and the aromatic dianhydride A to the solvent A is 1:(2-10); ② Under nitrogen atmosphere, room temperature and stirring conditions, the solvent A / tertiary amine A mixture and the aromatic diamine are mixed for 0.5h to 1h to obtain a mixture A, the reaction temperature is raised to 40°C to 80°C, and under nitrogen atmosphere, the temperature is 40°C to 80°C and stirring conditions, the aromatic dianhydride A is added to the mixture A in three portions and stirred for 2h to 5h. Finally, under nitrogen atmosphere, the reaction temperature is lowered from 40°C to 80°C to 25°C to 30°C, and the mixture is allowed to stand for 5h to 10h to obtain a polyamic acid salt solution containing a rigid chain; 2. Preparation of fluorine-containing polyamic acid salt solution: ① Weigh tertiary amine B, fluorinated diamine, aromatic dianhydride B and solvent B; mix solvent B and tertiary amine B to obtain a solvent B / tertiary amine B mixture; The molar ratio of the fluorinated diamine to the aromatic dianhydride B is 1:(0.9-1.2); the molar ratio of the fluorinated diamine to the tertiary amine B is 1:(0.05-2); the mass ratio of the total mass of the fluorinated diamine and the aromatic dianhydride B to the solvent B is 1:(2-10); ② Under nitrogen atmosphere, room temperature and stirring conditions, the solvent B / tertiary amine B mixture and the fluorinated diamine are mixed for 0.5h to 1h to obtain a mixture B, the reaction temperature is raised to 40°C to 80°C, and under nitrogen atmosphere, the temperature is 40°C to 80°C and stirring conditions, the aromatic dianhydride B is added to the mixture B in three portions and stirred for 2h to 5h. Finally, under nitrogen atmosphere, the reaction temperature is lowered from 40°C to 65°C to 25°C to 30°C, and the mixture is allowed to stand for 5h to 10h to obtain a fluorinated polyamic acid salt solution; 3. Weighing: Weigh 100 parts of a polyamic acid salt solution containing a rigid chain, 50 to 100 parts of a polyamic acid salt solution containing fluorine, and 0.5 to 2 parts of an aliphatic diamine according to the mass ratio; 4. Blending: Under the conditions of a temperature of 40° C. to 80° C., mechanical stirring and ultrasonic dispersion, the weighed aliphatic diamine is added to the polyamic acid salt solution containing a rigid chain, and stirred for 2 h to 5 h. Then, under the conditions of a temperature of 40° C. to 80° C., mechanical stirring and ultrasonic dispersion, the fluorine-containing polyamic acid salt solution is added. Finally, the reaction temperature is lowered from 40° C. to 80° C. to 25° C. to 30° C. to obtain a reaction system.
5. Freeze drying: The reaction system is placed in a mold, and then a freeze dryer is used to freeze the reaction system at a freezing temperature of -50°C to -10°C for 10 hours to 15 hours, and finally freeze-dried at a temperature of -30°C to -10°C for 60 hours to 100 hours to obtain a polyimide precursor aerogel.
6. Thermal imidization reaction: The polyimide precursor aerogel is subjected to a thermal imidization reaction to obtain a low CTE polyimide aerogel substrate.
9. The method for preparing a low CTE polyimide aerogel substrate according to claim 8, characterized in that Step 1② Add aromatic dianhydride A to mixture A in three portions at 1 / 2, 1 / 4, and 1 / 4 of the mass; Step 2② Add aromatic dianhydride B to mixture B in three portions at 1 / 2, 1 / 4, and 1 / 4 of the mass.
10. The method for preparing a low CTE polyimide aerogel substrate according to claim 8, characterized in that The thermal imidization reaction described in step six is specifically carried out according to the following steps: first, at a temperature of 70°C to 100°C, the constant temperature is 2h to 4h, then at a temperature of 180°C to 230°C, the constant temperature is 2h to 4h, then at a temperature of 300°C to 320°C, the constant temperature is 2h to 6h, and finally at a temperature of 400°C to 420°C, the constant temperature is 2h to 3h.